2019
DOI: 10.1021/acs.oprd.9b00498
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 1-[(Triisopropylsilyl)ethynyl]-1,2-benziodoxol-3(1H)-one (TIPS-EBX): Process Safety Assessment and Impact of Impurities on Product Stability

Abstract: The hypervalent iodine reagent 1-[(TriIsoPropylSilyl)Ethynyl]-1,2-BenziodoXol-3(1H)-one (TIPS-EBX) is among the most useful electrophilic and somophilic alkynylation reagents. Herein, we report a new synthetic protocol to access this reagent in one step from standard commercially available reagents. Thermal analysis of the synthesis procedure showed only weak exotherms. The compound could be obtained with high purity and stability using this new protocol, but care had to be taken to remove tosylate salts impur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
(40 reference statements)
0
9
0
2
Order By: Relevance
“…Recently, ethynylbenziodoxolones (EBXs) have emerged as useful, bench-stable radical alkynylating reagents that can be accessed via established synthetic methodologies . In 2014, Chen and Yu developed C­(sp 3 )–H alkynylations using EBXs [Figure B­(b)] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ethynylbenziodoxolones (EBXs) have emerged as useful, bench-stable radical alkynylating reagents that can be accessed via established synthetic methodologies . In 2014, Chen and Yu developed C­(sp 3 )–H alkynylations using EBXs [Figure B­(b)] .…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] DSC is considered ascreening technique,with limited sensitivity,but the results are accurate and robust enough to determine process temperatures to avoid thermal decomposition (often using T D24 :the temperature at which the time to maximum decomposition rate under adiabatic conditions is 24 h), [5] estimate the severity of an exotherm (often using the adiabatic temperature rise, DT ad ), [5] and even make predictions whether impact sensitivity and explosivity are aconcern by using the Yoshida correlation. [6] Such data, particularly on novel or underexplored compounds and reagents,isinformative to chemists wishing to employ new synthetic methods.T here are other thermal hazard tests available,s uch as accelerating rate calorimetry (ARC), reaction calorimetry,i mpact sensitivity or explosivity tests,b ut none are as ubiquitous or simple to use as the humble DSC.R ecently,t here have been studies seeking to characterise and compare the thermal and process hazards of compound classes,s uch as peptide-coupling reagents, [7] oxidisers, [8] N-heterocyclic iodanes, [9] diazo compounds, [10] and cage alkyl motifs; [11] or processes such as Pdcatalysed cross-coupling, [12,13] TIPS-EBX [14] and NaH with DMF/DMSO/DMAc. [15] In contrast to these in-depth studies,DSC data reported in the mainstream organic chemistry literature generally forms asmall part of amuch broader demonstration of the synthetic utility of areagent or process,perhaps used to make cautious statements about the stability or hazardous nature of ar eagent.…”
mentioning
confidence: 99%
“…Our group later reported a similar protocol but using commercially available terminal alkyne 6 for the synthesis of TIPS-EBX (4a) on multigram scale ( Scheme 3C ). 40 However, lower yields were obtained with alkyl or aryl substituted alkynes with this protocol and the Olofsson or Zhdankin protocols are usually preferred to synthesize them.…”
Section: Development Of Alkynyl Hypervalent Iodine Reagentsmentioning
confidence: 99%